2016
DOI: 10.4103/2229-516x.186961
|View full text |Cite
|
Sign up to set email alerts
|

Impact of self-assessment by students on their learning

Abstract: Context:Tutor assessment is sometimes also considered as an exercise of power by the assessor over assesses. Student self-assessment is the process by which the students gather information about and reflect on their own learning and is considered to be a very important component of learning.Aim:The primary objective of this study was to analyze the impact of self-assessment by undergraduate medical students on their subsequent academic performance. The secondary objective was to obtain the perception of studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 8 publications
4
60
0
14
Order By: Relevance
“…This result emphasises Ross (2006), Willey & Gardner (2009), Azarnoosh (2013, Sharma et al (2016), and Li & Chen (2016) that the accurate implementation of self and peer assessment is able to enhance students' enthusiasm, motivation and confidence to learn. Additionally, it can affect on a more autonomous learning (Honsa, 2013;Azarnoosh, 2013;Panadero et al, 2012).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…This result emphasises Ross (2006), Willey & Gardner (2009), Azarnoosh (2013, Sharma et al (2016), and Li & Chen (2016) that the accurate implementation of self and peer assessment is able to enhance students' enthusiasm, motivation and confidence to learn. Additionally, it can affect on a more autonomous learning (Honsa, 2013;Azarnoosh, 2013;Panadero et al, 2012).…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, time constraint was also stated as the challenge to give assessment and feedback in the classroom, so they could not be very complete and detailed, thus they could not be very objective, too. This finding echoes Sharma et al (2016) and Li & Chen (2016) that the most obvious limitation of using self and peer assessment is the difficulty of implementing it with a large group of students, thus it spends much time. Luckily, the video recording as advocated by Orlova (2009) could help them to observe the teaching performance more thoroughly, so that they could reflect more in a written form as a report.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…We observed that signs of lack of motivation (e.g., thoughts of dropping out, dissatisfaction with the course, decreased academic efficacy) and lack of emotional support were associated with MHP, as in medical students from other countries. 9 The use of portfolios, 100 self-assessments, 101 and continued mentorship 102 in undergraduate medical education could improve students' engagement and reflection about the course, alleviating sources of distress and helping students perceive their coursework as a gratifying activity. A drop in academic performance can be an indicative of a mental disorder.…”
Section: Discussionmentioning
confidence: 99%